PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Tahun 2017-2021) - Felicia Handoyo; Akram Akram; Nurabiah Nurabiah (Jurnal Riset Akuntansi, 2022)
The purpose of this study was to determine the effect of environmental performance and environmental disclosure on company profitability (study on mining companies listed on the Indonesia Stock Exchange in 2017-2021). This study is an associative research with a quantitative approach. This study uses secondary data in the form of annual reports and sustainability reports of mining sector companies listed on the Indonesia Stock Exchange during the 2015-2019. The sample used in this study consisted of 7 company samples, which were obtained based on the purposive sampling method. Thus, this study obtained 35 observation units during the five years of the study periods. The results of this study based on multiple linear regression analysisindicate. The research result showed that environmental performance and environmental disclosure have no effect on company profitability.